Variation of Heat Flux at Lower Frequencies of Vibration in a Vibrated Granular Bed - Nadeem Ahmed Sheikh; Shehryar Manzoor; Muzaffar Ali (Advances in Condensed Matter Physics, 2015)
Granular flows in vibrated bed exhibit various physical phenomena primarily driven by vibrating base. As the vibrating surface is the only source of energy in an otherwise dissipative flow, most of the theoretical models relate the steady state energy input to the RMS velocity of vibration. Here variation of heat flux is studied at varying frequency of vibration while keeping the RMS vibration velocity and the cell loading constant. Using single particle analysis and MD simulations, an extended version of grain-base collision is observed resulting in the reduction of heat flux at lower frequencies (<50 Hz) of vibration. The presented findings are important as most experimental studies are reported at these frequencies of excitation.